2015
DOI: 10.1590/1807-3107bor-2015.vol29.0070
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorder and anxiety, quality of sleep, and quality of life in nursing professionals

Abstract: To evaluate the association between temporomandibular disorder (TMD) and anxiety, quality of sleep, and quality of life in nursing professionals at the Hospital de Clínicas de Uberlândia of the Universidade Federal de Uberlândia -HCU-UFU (Medical University Hospital of the Federal University of Uberlândia), four questionnaires were given to nursing professionals. The questionnaires were completed by 160 of these professionals. The Fonseca's questionnaire was used to evaluate the presence and severity of TMD, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 17 publications
(28 reference statements)
1
35
1
10
Order By: Relevance
“…The FAI was used as the screening tool for TMD due to its simplicity, low cost and high efficiency in obtaining epidemiologic data in a short time . It has been employed in many previous studies on TMD prevalence in other target population . Based on the FAI, 58.2% of participants showed no symptoms of TMD, whereas 41.8% had mild to moderate TMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAI was used as the screening tool for TMD due to its simplicity, low cost and high efficiency in obtaining epidemiologic data in a short time . It has been employed in many previous studies on TMD prevalence in other target population . Based on the FAI, 58.2% of participants showed no symptoms of TMD, whereas 41.8% had mild to moderate TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors including facial trauma, lack of physical activity, living with single or divorced parents, prolonged computer usage had likewise been associated with TMD in adolescents . TMD had been found to negatively affect quality of life (QoL) and are linked to poor sleep quality in South American nursing students . Rocha et al found a high prevalence of TMD (58.9%) among South American dental students that affected their general health, anxiety states and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Para qualidade de vida, uma associação foi encontrada entre deslocamento de disco com redução e o domínio social; já os domínios físicos foram associados com DTM muscular 15 . Oliveira et al 46 Para compreender e gerenciar pacientes com disfunção temporomandibular é necessário entender a disfunção temporomandibular suas comorbidades, como também observar a qualidade de vida. As implicações desta disfunção são graves, principalmente em relação às condições crônicas, assim o uso de estratégias de gestão biopsicossocial para reduzir dor e melhorar a função é a abordagem que tem demonstrado sucesso para a maioria dos casos 47 .…”
Section: Discussionunclassified
“…It has been suggested that this can affect the patterns of muscle activation in TMD patients, leading to tension-related headaches. Oliveira et al (29) stated that TMD has a negative effect on the quality of sleep and quality of life. Lei et al (30) investigated the prevalence of sleep disorders among TMD patients and con irmed that the two variables were correlated, given that the frequency of sleep disorders was signi icantly higher among those with TMD, when compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%